A CASE STUDY AND CHALLENGES IN REPORTING OF ANO-RECTAL DISORDERS - Suman Yadav; Ashutosh Kumar Yadav; Vishal Tiwari (AYUSHDHARA, 2020)
Ano-rectal disorders namely Haemorrhoids, Fissure-in-ano and Fistula-in-ano here includes a variety of pathological disorders having different and various types of clinical presentation. These ano- rectal disorders generates relevant discomfort and disability to the patient. In this work our primary focus is only on these three anorectal disorders. The prevalence of Ano- rectal disorders are much higher than what we see in the hospital or clinics because most of the patient having such disorders do not seek for medical attention at an early stage. The present paper discusses about the hurdles or challenges faced while trying to enroll, update and increase the cases of Haemorrhoids, Fissure-in-ano and Fistula-in-ano reporting to Shalya Tantra OPD and IPD of Government Ayurvedic College and Hospital, Varanasi between year 2009-2019. The study had been also carried out to know the prevalence of diagnosed cases of Haemorrhoids, Fissure-in-ano and Fistula-in-ano and the interpretation of the data on the gender basis for better understanding of the disease. It is an institutional data study of total 5158 patients with an aim to estimate and evaluate the epidemiology of these ano–rectal disorders in eastern UP. This work is exploring scientifically the cause behind the prevalence of these three ano-rectal diseases reporting in our hospital.